Use of a Novel Application Technique of MatriDerm to Improve Handling and Ease - Joanneke Maitz, MD, MPhil; Lucas Carelli, MD; Elizabeth Coady, MD; Duncan Loi, MD; Peter Maitz, MD, FRACS, AM (Plastic and Reconstructive Surgery, Global Open)
Background:. MatriDerm is frequently used with a split-thickness skin graft (STSG) in a 1-stage procedure and has been clinically shown to improve the quality and appearance of reconstructed tissue. However, its fragile nature makes it challenging to use, especially when in contact with moisture or wound exudate. Recently, a novel composite application technique was described to improve the handling and ease of use of MatriDerm in a single-stage procedure. This case series uses the new application technique and discusses its outcomes. Methods:. Four patients admitted between October 2022 and December 2022 to the burns and reconstructive surgery unit of Concord Repatriation General Hospital received MatriDerm applied with the new technique to their deep dermal and full-thickness injuries. All injuries were sustained by a burn, encompassing 1% total body surface area or less, and varied in anatomical location: shin, ankle, hand, and knee. Results:. Complete wound closure was achieved in all patients using the new composite application technique. The method allowed for more efficient operating time, with less skin graft manipulation than the standard application technique recommended by the manufacturer. Conclusions:. The results demonstrate the efficacy of a composite application technique combining MatriDerm with STSGs as a 1-stage solution for deep dermal and full-thickness wound treatment, especially in challenging anatomical areas such as digits or over joints. Initial findings suggest comparable graft success rates to standard STSG results. Despite its promising outcome, further investigations with more significant case numbers are required to further evaluate its safety, efficacy, and cost-effectiveness.